DEVELOPMENT SYSTEM MODELS AS A BASIS ORGANIZATIONAL-TECHNOLOGICAL SYSTEMS CONTROL THE LIFE CYCLE OF AN AERONAUTICS - Тамаргазін, О.; Крамаренко, Т. (Science-based technologies, 2011)
In the article the gear of interacting of organizational-technological systems in structure of life cycle of a modern aeronautics is observed. It was thus considered, that the structure vital to an aeronautics cycle charac-terizes it as an element of hierarchical system in structure of all air-transport complex. The analysis of this prob-lem has allowed to open gears direction of operation achievement and to determine the primary goals of inte-gration of organizational-technological systems on all stages of life cycle of an aeronautics.